2017
DOI: 10.1109/jsen.2017.2669262
|View full text |Cite
|
Sign up to set email alerts
|

Microphone-Array Ego-Noise Reduction Algorithms for Auditory Micro Aerial Vehicles

Abstract: When a micro aerial vehicle (MAV) captures sounds emitted by a ground or aerial source, its motors and propellers are much closer to the microphone(s) than the sound source, thus leading to extremely low signal-to-noise ratios (SNR), e.g.-15 dB. While microphone-array techniques have been investigated intensively, their application to MAV-based ego-noise reduction has been rarely reported in the literature. To fill this gap, we implement and compare three types of microphonearray algorithms to enhance the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 37 publications
1
56
0
Order By: Relevance
“…Despite the performance with the audio 3, the obtained results showed that the proposed method presents a good performance, making able to retrieve the source location (within an error of 10°) in cases where the signal-to-noise ratio (SNR) was of -16 dB. This is aligned with the results obtained in [10], where methods of state-of-art had their performance reported.…”
Section: Discussionsupporting
confidence: 76%
“…Despite the performance with the audio 3, the obtained results showed that the proposed method presents a good performance, making able to retrieve the source location (within an error of 10°) in cases where the signal-to-noise ratio (SNR) was of -16 dB. This is aligned with the results obtained in [10], where methods of state-of-art had their performance reported.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, since the microphones are mounted on the drone itself, they are very close to the noise sources leading to high noise levels. Because of this, the SNR can easily reach -15 dB or less [11] making SSL very difficult. Another factor impacting localization performance is wind noise.…”
Section: A Challenges and Opportunities Of The Datasetmentioning
confidence: 99%
“…On the other hand, SSL is a long standing and extensively studied topics in robotics [18]. However, both ego-noise reduction and SSL for the specific setting of UAV-embedded microphones are still rather new topics [3], [19], [4], [14], [20], [5], [11], [11]. Many SSL approaches developed in recent years for robotics are different variations of the MUltiple SIgnal Classification (MUSIC) algorithm.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Beamforming technique is an important part of array signal processing. It is widely used in wireless communications [1], microphone array signal processing [2] and radar [3]. A typical, representative beamformer, known as minimum variance distortionless response (MVDR) or Capon beamformer [4], minimizes array output power and maintains a distortionless mainlobe response toward the desired signal.…”
Section: Introductionmentioning
confidence: 99%